Evaluation of dietary patterns and their impact on eye health among Saudi adults—A multi-regional cross-sectional analysis in Makkah, Riyadh, and Qassim - Thirunavukkarasu, Ashokkumar; Alanazi, Bader; Alfaleh, Abdulrahman; Alsulami, Hani Hathath; Albudayr, Sulaiman Abdullah; Alotaibi, Abdulrahman Saad; Alenezi, Reema Mohammed; Alruwaili, Araa Ghanem; Alibrahim, Noor Oqalaa (Frontiers in Nutrition, 2024)
Background and aim: Nutrition plays a vital role in maintaining and improving vision health. However, little is known about dietary intake habits and their correlation with vision health among adults in the Kingdom of Saudi Arabia (KSA). The present survey was aimed to assess dietary patterns and vision health among Saudi adults and to determine the association between dietary patterns and vision health. Methods: The present analytical study was carried out among 1234 Saudi adults in the Makkah, Riyadh, and Qassim regions of KSA. We used the Arabic version of the National Eye Institute Visual Functioning Questionnaire-25 (NEI VFQ-25) and the Diet Quality Screener (DQS). We applied Mann Whitney U and Kruskal Wallis tests to determine the association between vision function score and demographic characteristics. Furthermore, the Spearman correlation test was used to determine the relationship between the DQS and the NEI VFQ-25. Results: Of the studied population, the highest score obtained through the NEI VFQ-25 was in the social function domain (mean ± SD = 76.64 ± 18.63), followed by the general vision domain (mean ± SD = 75.21 ± 15.16) and was negatively correlated with age. Regarding dietary patterns, the intake of lean protein sources per week was the highest, with a mean intake of 4.17 days per week, followed by that of whole grains and milk or dairy products, with a mean intake of around four days per week. There was a significant correlation between various dietary intakes and visual function scores. Conclusion: The present survey underscores the significance of understanding regional dietary patterns and their implications for vision health. Furthermore, our study's findings indicate a need for targeted nutritional intervention measures to improve the vision health of this population.